Análise icnológica do intervalo Siluriano-Devoniano da Bacia do Paraná e sua aplicabilidade em estudos de variações relativas do nível do mar - Sedorko, Daniel (Universidade do Vale do Rio dos Sinos, 2018)
This thesis has as its main approach the use of ichnological data as indicators of stratigraphic signatures, paleoenvironmental parameters and relative paleobathymetry, and aims, mainly, to diagnose changes in ichnological suites along the SiluroDevonian of the Paraná Basin. Based on the hypothesis that the ichnological analysis allows inferences of sea level oscillations on a larger scale (3rd or 2nd order), the Siluro-Devonian succession (Furnas and Ponta Grossa formations) was prospected, focusing on the Campo Gerais region of Paraná. to investigate its faciological, ichnological and fossiliferous composition. This integrated analysis enabled the diagnosis of key stratigraphic signatures (eg Glossifungites in sequence limits, dense occurrence of Zoophycos in the treatment of high-level or low accommodation space systems; Lingulichnus in the treatment of transgressive systems or finning upward cycles), as well as it allowed the definition of paleoenvironments (mainly reinforcing the marine context of the Furnas Formation) and ichnostratigraphic zones (defining the Lower Silurian age for the lower and middle units of the Furnas Formation). It also guided the recognition of third-order depositional sequences for the Paraná Supersequence. Specific studies were carried out on the northwestern edge of the basin (Mato Grosso do Sul) to compare with data from the southeastern edge (Paraná), attesting to the shallower character of the northern deposits. Paleocological data inferred by the ichnological analysis helped to understand paleobiological events, mainly related to faunal changes during the Devonian (Zlíchov Basal Event and the decline of Fauna Malvinocáfrica). In summary, this thesis demonstrates the potential of Ichnology to solve paleoenvironmental, paleobiological, ichnostratigraphic issues and to help define sequence frameworks.
Keywords: Icnologia; Siluriano; Devoniano; Colonização do ecoespaço; Paleobatimetria relativa; Ichnology; Silurian; Devonian; Ecospace colonization; Relative paleobathymetry; ACCNPQ::Ciências Exatas e da Terra::Geologia